Rancang Bangun Sistem Pengukur Arus dan Suhu Permukaan Laut Portable Berbasis Internet of Things - Leo Gumalto Butarbutar; Djoko Prabowo; Immanuel Jhonson Arizona Saragih (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2023)
The ocean plays a vital role in both the economy and the environment. Monitoring and understanding its conditions are crucial for preserving marine ecosystems and ensuring the security of marine resources. Measuring ocean currents and surface temperatures provides essential information for environmental modeling. Current research focuses on developing a portable Internet of Things (IoT) system for measuring ocean currents and surface temperatures. Traditional observation tools like sea gliders are expensive and bulky, while buoys lack portability. This study presents a simple IoT-based system utilizing sensors and the Arduino Mega 2560 microcontroller. The device effectively measures current speed, direction, surface temperature, and detects location coordinates. Measurement data is wirelessly transmitted in real-time to the ThingView application. These data serve to verify the Ocean Forecast System (OFS) model and improve the maritime services offered by the Indonesian Meteorological, Climatological, and Geophysical Agency (BMKG). The device's compact design facilitates direct acquisition of current and surface temperature data. It exhibits higher resolution than the OFS model, with current speed measurement resolution around 0.02 cm/s and surface temperature measurement resolution around 0.0625°C, while the OFS has resolutions of 5 cm/s and 2.0°C, respectively.